Identification of Tpack Ability in Middle School Science Teachers - Hikmah Fatimah; Emy Shofiah Setyowati; Bramastia Bramastia (INKUIRI: Jurnal Pendidikan IPA, 2023)
In carrying out learning, teachers are required to keep up with the times by integrating knowledge of content, pedagogy and technology into learning. The ability of TPACK is very influential on learning in the classroom. For this reason, the study was conducted to determine the TPACK ability of junior high school science teachers in Central Java and East Java Provinces. The sample was taken through the cluster sampling technique on 33 science teachers through a google form-based questionnaire with 43 TPACK indicators. The results of the analysis show that 87% of teachers have TPACK abilities with good criteria and 13% of teachers have TPACK abilities with poor criteria. The lack of TPACK ability in science teachers can be caused by several factors such as age, less than optimal training attended by teachers and gender. For this reason, it is hoped that the government can help teachers improve their TPACk skills so that the teaching and learning process can be carried out optimally according to the development of the times.